Uma metodologia para seleção e avaliação de software para apoiar o processo de inteligência competitiva nas fases da coleta e análise - Rossi, Jandira Ferreira de Jesus (2010)
The Competitive Intelligence (CI) is a systematic and ethical process of collection, storage and information analysis so that Organizations can obtain the competitive advantage in their businesses. For the application of this process, the CI is represented in a cycle which contains the phases of identification of necessities; planning; collections; analysis; dissipation and evaluation. The information volume to be collected and analyzed, the urgency to obtain results and the complexity of the studies of the CI, all point to the importance of the use of computer tools that support this activity. This research proposes a methodology to identify a tool that would facilitate the activities of the CI collectors and analysts, especially in the information extraction of texts needed in the transition between the phases of collection and analyses. The exploratory descriptive research was the methodology used in this work, divided into two parts: the theoretical methodology and the experimental. The first was applied to identify potential collaborating tools for the complete CI cycle and to extract information between the phases of collection and analysis. The second, to select and validate a tool (software). The tool selected was the software Zotero, which acts as an administration of bibliographica and citations reference. To validate this tool, an experiment was elaborated which contained two simulations involving the collection and extraction of information with and without the use of such tool. Two CI teams particpated in the simulations: one from Manaus and the other from São Carlos, with a total of 6 collects and 1 analyst. As a result, it was possible to identify that the software Zotero supports collectors and analysts in realizing the activities in the phases of collection and analysis.